2012
DOI: 10.1530/eje-12-0053
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of all-cause and site-specific cancer in type 2 diabetes: the Fremantle Diabetes Study

Abstract: Objective: To explore the relationship between diabetes and cancer. Design: The Fremantle Diabetes Study (FDS) was a community-based longitudinal observational study of 1426 subjects, 1294 of which had type 2 diabetes. Methods: The FDS type 2 cohort and four age-, sex-and postcode-matched controls per case were followed for cancer events from 1993 until mid-2010 and incidence rate ratios (IRRs) were calculated. Competing risks proportional hazards models generated risk factors for incident cancers in the diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 60 publications
1
24
0
3
Order By: Relevance
“…This review had several limitations. Whilst the selection criteria for the review were broad, they did not allow inclusion of data from papers looking at cancer and CCBs, where either breast cancer was not isolated as an outcome, or CCBs as the exposure (68)(69)(70)(71)(72)(73)(74). It is possible that this may have also led to some RCTs being omitted, though reviewing references of a recent systematic review and meta-analysis of relevant RCTs indicates that no eligible studies were missed (75).…”
Section: Discussionmentioning
confidence: 99%
“…This review had several limitations. Whilst the selection criteria for the review were broad, they did not allow inclusion of data from papers looking at cancer and CCBs, where either breast cancer was not isolated as an outcome, or CCBs as the exposure (68)(69)(70)(71)(72)(73)(74). It is possible that this may have also led to some RCTs being omitted, though reviewing references of a recent systematic review and meta-analysis of relevant RCTs indicates that no eligible studies were missed (75).…”
Section: Discussionmentioning
confidence: 99%
“…Four age-, sex- and zip-code-matched non-diabetic controls were randomly selected from this source for each participant at the time of FDS1 study entry [25]. The requirement for zip-code matching was based on the fact that there are substantial socio-economic and environmental differences between residential districts within the FDS1 catchment area.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have revealed significant changes to intestinal epithelial cells (IECs) in DM rats (12,13). Recently, researchers have found that changes leading to colorectal cancer may be closely related to DM (14,15), supporting the hypothesis that there is a relationship between DM and abnormal differentiation of IECs.…”
mentioning
confidence: 86%